Facile in situ fabrication of biomorphic Co2P-Co3O4/rGO/C as an efficient electrocatalyst for the oxygen reduction reaction. Issue 7 (12th February 2020) - Guo, Xingmei; Qian, Cheng; Wan, Xiaohan; Zhang, Wei; Zhu, Haowei; Zhang, Junhao; Yang, Hongxun; Lin, Shengling; Kong, Qinghong; Fan, Tongxiang
Abstract : Biomorphic Co2 P-Co3 O4 /rGO/C, consisting of Co2 P-Co3 O4 heterogeneous particles and rGO sheets on a C substrate, is in situ fabricated using G+ bacteria as both a P source and template, which leads to good electrocatalytic performances for the ORR. Abstract : Streptococcus thermophilus, a Gram-positive (G+) bacterium featuring a teichoic acid-rich cell wall, has been employed as both a phosphorus source and template to synthesize a biomorphic Co2 P-Co3 O4 /rGO/C composite as an efficient electrocatalyst for the oxygen reduction reaction (ORR). Different from the conventional method for the synthesis of phosphides, bio-derivative phosphorus vapor was emitted from the inside out, which facilitated the in situ transformation of the chemically adsorbed Co precursor on the bacteria into Co2 P-Co3 O4 heterogeneous nanoparticles, which featured a Co2 P-rich body and Co3 O4 -rich surface. Besides, reduced graphene oxide (rGO) was also introduced in the synthetic process to keep Co2 P-Co3 O4 scattered and further promote the electron transport efficiency. All the Co2 P-Co3 O4 nanoparticles and rGO sheets were supported on the bacteria-derived carbon substrate with submicron-spherical morphology. The as-obtained Co2 P-Co3 O4 /rGO/C composite exhibited excellent electrocatalytic performance for ORR with onset and half-wave potentials of 0.91 and 0.80 V vs. RHE, respectively. Furthermore, its long-term stability and methanol tolerance were better than those of commercial Pt/C. Thus, this work presents a new strategy of using an interior bio-phosphorus source to obtain heterojunction particles featuring a phosphide-rich body and oxide-rich surface, which may provide some insights for the construction of efficient heterogeneous electrocatalysts.